2003
DOI: 10.1186/1472-6874-3-4
|View full text |Cite
|
Sign up to set email alerts
|

Delayed presentation in breast cancer: a study in Iranian women

Abstract: BackgroundA cross sectional study was conducted in Tehran Iran to examine the extent of patient delay and associated factors in the presentation of breast cancer.MethodsA group of newly diagnosed breast cancer patients were interviewed and were asked about the period from first onset of symptoms to first medical consultation to indicate patient delay. This was studied in relation to patients' age, educational level, marital status, family history of breast cancer, history of benign breast disease, number of ch… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

12
99
1
2

Year Published

2005
2005
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 113 publications
(114 citation statements)
references
References 27 publications
12
99
1
2
Order By: Relevance
“…This was done because delay more than 12 weeks has been shown to result in advanced disease and worse survival. 3 …”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…This was done because delay more than 12 weeks has been shown to result in advanced disease and worse survival. 3 …”
Section: Methodsmentioning
confidence: 99%
“…It has been proven that patients with longer duration of symptoms present with more advanced disease and that a delay in diagnosis between 3-6 months after onset of symptoms reduces 5-years survival by 7% compared to patients diagnosed within 3 months of onset of symptoms. 3,4 Overall in the western population there has been a fall in deaths caused by breast cancer as a result of breast screening, early diagnosis and better treatment although the relative contribution of these factors is yet to be evaluated. 5 Lack of a screening program and delay in diagnosis is hindering attempts to improve breast cancer survival in India.…”
Section: Thiruvananthapurammentioning
confidence: 99%
“…The results of two studies showed that 25% (Montazeri et al, 2003) to 42.5% (Harirchi et al, 2005) of Iranian women do not seek medical help until three months or more after initial detection of breast symptoms. Delayed presentation is accompanied with late stage of disease, high mortality (Montazeri et al, 2003) and lower survival (Babu et al, 2011).…”
Section: Introductionmentioning
confidence: 99%
“…Delayed presentation is accompanied with late stage of disease, high mortality (Montazeri et al, 2003) and lower survival (Babu et al, 2011). Therefore, symptom detection by patients and early response to self-discovered symptoms is important modality to the early diagnosis of breast cancer.…”
Section: Introductionmentioning
confidence: 99%
“…Breast cancer survival rates of women in Asia are approximately half of their Western counterparts (Parkin et al, 2005;Green and Raina, 2008). In Iran, breast cancer is recognized as one of the fastest increasing and the most important women's health issues (Montazeri et al, 2003). Having a mortality rate of 4 per 100,000, breast cancer is the fifth leading cause of death and the third source of burden in malignant diseases for Iranian women (Akbari et al, 2011).…”
Section: Introductionmentioning
confidence: 99%